2007
DOI: 10.1021/ic7011815
|View full text |Cite
|
Sign up to set email alerts
|

Archetypical Modeling and Amphiphilic Behavior of Cobalt(II)-Containing Soft-Materials with Asymmetric Tridentate Ligands

Abstract: The stabilization of a bivalent oxidation state in cobalt complexes of phenolate-based asymmetric tridentate ligands with iodo and bromo substituents is studied. The complexes [CoII(LIA)2].2CH3OH (1) and [CoII(LBrA)2].CH3OH (2) were characterized by means of several spectroscopic and spectrometric techniques. The molecular structure of 1 was determined by diffractometric analysis and reveals the cobalt(II) ion in a distorted-octahedral geometry. The centrosymmetric metal ion adopts a local D2h symmetry and is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 47 publications
3
36
0
Order By: Relevance
“…Similarly, the archetypical ligands were synthesized with 80-85 % yields following literature procedures [17,20,21] and characterized by means of ESI mass spectrometry, 1 H NMR, and infrared spectroscopy. ticularly visible at low cone voltages.…”
Section: The Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the archetypical ligands were synthesized with 80-85 % yields following literature procedures [17,20,21] and characterized by means of ESI mass spectrometry, 1 H NMR, and infrared spectroscopy. ticularly visible at low cone voltages.…”
Section: The Ligandsmentioning
confidence: 99%
“…Nevertheless, the small body of work available on the isolation and air/water interface behavior of metallosurfactant precursors still poses a major drawback to the approach. [13,14] At the forefront of this area, our group has focused on synthetic, modeling, and surface protocols involving the incorporation of magnetic µ-oxo-Cu 4 clusters in LangmuirBlodgett films, [15,16] the observation of distinctive collapse mechanisms on cobalt(II) films, [17] and the design of redoxactive copper-containing amphiphiles. [18,19] In a series of studies with iron(III), [20] cobalt(II/III), [21] and gallium-(III) [22] we have demonstrated that structural and electronic effects can determine the preferential geometry of redoxactive asymmetric NNЈO ligands in [ML 2 ] metallosurfactants.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated the feasibility of Langmuir-Blodgett (LB) films with magnetic copper(II) clusters, [27] the redox-state control and dependence of a collapse mechanism on cobalt(II) films, [28] and the factor that determines the delicate equilibrium between redox activity and amphiphilicity in copper/phenoxyl species. [29] Herein, we present an in-depth investigation of the properties of novel single-tail cationic copper(II)-containing surfactants with the ligands L PyC 18 , L PyC 16 , L PyC 14 , and L PyC 10 , in which Py = pyridine and C n indicates the alkyl chain length.…”
Section: CL 2 a C H T U N G T R E N N U N G (L Pyc 14 )] (3) [Cu mentioning
confidence: 99%
“…Overall, the C 16 species start organizing at lower area per molecule values and collapse at slightly lower pressures than their C 18 counterparts, which thus reflects the influence of the chain length. In contrast to 1 and 4, species 2 and 5 display similar A c values of [26][27][28] 2 at collapse, with 5 showing a steeper slope. The reported collapse pressures for 1, 2, 4, and 5 are significantly greater than those observed for other metal-surfactant complexes.…”
mentioning
confidence: 91%
“…Therefore, the fact that we have observed a signal indicates the presence of Co(II) ions. 30 The EPR spectra of 1(a and b) interpreted in terms of g values displays g II 5 2.9431 and g \ 5 2.548, characteristic of pseudo-octahedral cobalt complexes. No hyperfine splitting with the cobalt nucleus (I 5 7/2) was observed, which suggests that the exchange interaction between Co(II) ions is large enough to collapse this interaction into a single line.…”
Section: Electron Paramagnetic Resonance Spectroscopymentioning
confidence: 99%